2002
DOI: 10.1006/jcph.2002.7131
|View full text |Cite
|
Sign up to set email alerts
|

3D Analysis of Crystal/Melt Interface Shape and Marangoni Flow Instability in Solidifying Liquid Bridges

Abstract: This version is available at https://strathprints.strath.ac.uk/62646/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…The concentration distribution, however, was found to be azimuthally distorted from a ''macroscopic'' point of view. The numerical results 19 have confirmed that the steady bifurcation of Marangoni flow can affect the crystallization process.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The concentration distribution, however, was found to be azimuthally distorted from a ''macroscopic'' point of view. The numerical results 19 have confirmed that the steady bifurcation of Marangoni flow can affect the crystallization process.…”
Section: Introductionsupporting
confidence: 85%
“…This was proved from an experimental point of view by Camel et al 18 and confirmed by the numerical simulations of Lappa and Savino. 19 ''Weak laminar nonaxisymmetric convection'' in the liquid phase may induce radial segregation with a nonaxisymmetric distribution. 18 Experiments showing these behaviors were carried out during the German Spacelab Mission D-2.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as demonstrated from an experimental point of view by Camel et al [19] and confirmed by the numerical simulations of Lappa and Savino [20], also this instability can play a ''critical role'' in the crystallization process (the steady bifurcation of Marangoni flow in fact can be responsible for the azimuthal distortion of the melt/crystal interface at macroscopic length scale).…”
Section: Introductionmentioning
confidence: 77%
“…The free interface was assumed to be cylindrical in these studies and the azimuthal wave number (m) was found to behave as a decreasing function of the aspect ratio i.e. 2mA=const; Lappa and Savino [67] extended such a relationship to the case of dynamical aspect ratio changes induced by solidification. Imaishi et al [68] depicted in detail the complex spatio-temporal evolution of the flow field that occurs after the secondary (oscillatory) bifurcation of the Marangoni flow for different values of the aspect ratio A and of the Prandtl number (0≤Pr≤0.02), elucidating different (referred to as "torsional") oscillatory behaviours (Fig.…”
Section: Half-zonementioning
confidence: 99%